Academic Drift in China’s Universities of Applied Technology - Jing, Wei; Welch, Anthony (International Higher Education, 2018)
The priority attached to innovation in China means that its universities are seen as a major pillar of innovation. But with respect to the new Universities of Applied Technology (UATs), their original mission of strengthening industry collaboration is subverted by the persistence of perverse incentives, which make them emulate research universities rather than fulfil their original purpose.